The experiential perspectives of siblings and partners caring for a loved one with an eating disorder in the UK. Issue 2 (24th March 2022) - Batchelor, Rachel; Cribben, Hannah; Macdonald, Pamela; Treasure, Janet; Cini, Erica; Nicholls, Dasha; Kan, Carol
Abstract : Background: Caring for a loved one with an eating disorder typically comes with a multitude of challenges, yet siblings and partners are often overlooked. It is important to understand if current clinical guidance for supporting carers are effective and being utilised for these groups, to help meet their needs. Aims: To identify the experiential perspectives of siblings and partners of a loved one with an eating disorder compared with guidance for improving the adequacy of support provided to carers published by Beat and Academy for Eating Disorders. Method: Three online focus groups were held for ten siblings and five partners from across the UK (12 females and three males). Carers had experience of caring for a loved one with anorexia nervosa (13 carers) or bulimia nervosa (two carers), across a range of therapeutic settings. Focus group transcriptions were analysed with thematic analysis. Results: Four key themes were identified: (a) role-specific needs, (b) challenges encountered by siblings and partners, (c) generic needs and helpful strategies or approaches, and (d) accounts of service provision and family support. Conclusions: Overall, the majority of experiences reported by siblings and partners did not meet the published guidance. Consequently, clinical practice recommendations were identified for services, alongside the charity sector, to take a proactive approach in detecting difficulties, providing skills training and emotional/practical support, adapting/tailoring peer support groups and supporting online facilitation. Our findings part-informed the design of our national online survey on loved ones' experiences of care in eating disorders.